2020
DOI: 10.1186/s12998-019-0293-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a single spinal manipulation on cardiovascular autonomic activity and the relationship to pressure pain threshold: a randomized, cross-over, sham-controlled trial

Abstract: Background: The autonomic nervous system interacts with the pain system. Knowledge on the effects of high velocity low amplitude spinal manipulations (SM) on autonomic activity and experimentally induced pain is limited. In particular, the effects of SM on autonomic activity and pain beyond the immediate post intervention period as well as the relationship between these two outcomes are understudied. Thus, new research is needed to provide further insight on this issue. Objectives: The aim was to assess the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 52 publications
0
19
0
6
Order By: Relevance
“…However, two systematic reviews suggest that such effects, if they occur, are short-lasting and without clinical consequences [ 13 , 20 ]. Moreover, a recent randomized controlled trial which compared SMT to a successful sham control found no such effect [ 21 ]. Although essential to the understanding of physiological mechanisms of action of interventions, laboratory experiments alone have not provided a mechanistic understanding of these hypotheses nor provided evidence of clinical efficacy or effectiveness [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, two systematic reviews suggest that such effects, if they occur, are short-lasting and without clinical consequences [ 13 , 20 ]. Moreover, a recent randomized controlled trial which compared SMT to a successful sham control found no such effect [ 21 ]. Although essential to the understanding of physiological mechanisms of action of interventions, laboratory experiments alone have not provided a mechanistic understanding of these hypotheses nor provided evidence of clinical efficacy or effectiveness [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the present report deals only with information relevant to the pain perception study. For more details, please see Picchiottino et al, 2019 [12]. The study was approved by the ethics committee EA 4532 of the University Paris Sud UFR STAPS, Orsay, France (October, 2016), registered as a clinical trial at https://clinicaltrials.gov (Registration NCT03776708), and, as required by French law, insured by HDI global assurance (N°01012787-14,009).…”
Section: Design Ethics Committee and Registrationmentioning
confidence: 99%
“…The data collection also included autonomic nervous system variables [12], so the students were informed not to ingest food, caffeine, alcohol, or tobacco in the hour prior to the sessions, as well as not to perform intense physical activity the day of the experimentation.…”
Section: Inclusion and Non-inclusion Criteriamentioning
confidence: 99%
“…Autonomic nervous system it’s a part of the central nervous system, and can be divided in three parts: the enteric-, parasympathetic- and the sympathetic nervous system, [ 39 ] and ensures the perfect physiologic harmony translated in homeostasis by working antagonistically [ 40 ]. ANS can be studied by several non-invasive methods, such as heart rate variability (HRV), cardiovagal, adrenergic, and sudomotor tests [ 31 ] plasma catecholamines, Electrodermal activity, blood pressure changes [ 41 ] and two new protocols described by Ghiasi & Cols.…”
Section: Introductionmentioning
confidence: 99%